Improving oxygen reduction reaction of microbial fuel cell by titanium dioxide attaching to dual metal organic frameworks as cathode. (April 2022) - Yang, Jiaqi; Chen, Junfeng; Wang, Xuemei; Yang, Daoxin; Zhang, Yiwen; Wu, Yiqun; Zhao, Yongyue; Wang, Yongle; Wei, Qingying; Wang, Renjun; Liu, Yanyan; Yang, Yuewei
Graphical abstract: Highlights: TiO2 shell encased dual MOFs core was prepared by distribution feeding method. TiO2 @ZIF-67/ZIF-8 was integrity, stability and great electrochemical activity. Maximum power density of TiO2 @ZIF-67/ZIF-8-MFC was 341.506 mW/m 2. TiO2 @ZIF-67/ZIF-8 increased active sites, specific surface area and catalytic activity. Abstract: In this study, a two-step simple distributed feeding method was used to prepare the core–shell nanocomposite dual metal organic frameworks (D-MOFs, TiO2 @ZIF-67/ZIF-8). There were three obvious peaks (0 1 1), (1 1 2), (2 2 2) interface in D-MOFs core, which fully showed that ZIF-67/ZIF-8 crystal core was successfully synthesized. The morphology of composite material was core–shell structure with a rough surface, and Ti, Co, Zn, Al were uniformly distributed on the surface. TiO2 @ZIF-67/ZIF-8 also had excellent electrochemical activity and the maximum power density of TiO2 @ZIF-67/ZIF-8 microbial fuel cell (MFC) was 341.506 mW/m 2, which was 1.30 times of ZIF-67/ZIF-8-MFC (262.144 mW/m 2 ) and 2.07 times of ZIF-67-MFC (164.836 mW/m 2 ). And the continuous output voltage of TiO2 @ZIF-67/ZIF-8-MFC was 413.43 mV, which could maintain stable voltage output for 8.3 days. D-MOFs as the core of composites ensured the integrity, stability and high activity of materials; Rough TiO2 as the surface of the material provided surface area and reaction center.